(untitled) (Research, Society and Development, 2020)
This article presents the actions developed in an extension project, promoted by a study group from a State University in Paraná. Named “Evaluative Coffee”, project was attended by students and teachers from Higher Education and Basic Education. The objective was to provide participants with moments of reflection on evaluative practices, conceptions and alternative evaluative actions, above all, of a diagnostic and formative nature. To this end, seven meetings were planned and held, which took place in face-to-face. In order to theoretically support the project activities, articles and book chapters from researchers investigating Educational Evaluation were used. The nature of this research is qualitative and Textual Discursive Analysis was used to analyze the data collected from the participants who answered a questionnaire applied in the last meeting. As a result of the analysis, it was possible to infer that evaluation is a topic that concern teachers, teachers desire more knowledge regarding the theme of educational evaluation, both in the theoretical and practical sense and alternative evaluation practices are welcome in the school context.